Sarcoidosis: a pattern of clinical and morphological presentation. Issue 3 (March 1987) - Valantine, H; McKenna, W J; Nihoyannopoulos, P; Mitchell, A; Foale, R A; Davies, M J; Oakley, C M
Abstract : The diagnosis of cardiac sarcoidosis, particularly when there is no overt systemic involvement, is frequently delayed because of its varied manifestations. Focal left ventricular wall motion abnormalities were recognised in five patients with sarcoidosis. Three patients showed abnormal regional wall motion in the basal portion of the ventricular septum and free wall with sparing of the apex. The angiographic appearances supported the echocardiographic findings which were atypical of ischaemic heart disease. The remaining two patients both had diffuse left ventricular hypokinesia, with a focal abnormality that was most pronounced in the anteroapical region; this pattern is often seen with coronary disease. The recognition by echocardiography or angiography of focal abnormalities of wall motion affecting the basal portion of the ventricular septum should suggest the possibility of myocardial sarcoidosis even in the absence of recognised systemic manifestations.